(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Manuhutu JF, Wiadnya DGR, Sambah AB, Herawati EY. 2021. The presence of whale sharks based on oceanographic variations in Cenderawasih Bay National Park, Papua, Indonesia. Biodiversitas 22: 4948-4955. Oceanographic factors have an important role in the study of estimating the distribution of fish resource habitats. Sea Surface Temperature (SST), Sea Surface Chlorophyll (SSC), Current Speed, Sea Surface Height (SSH), and bathymetry are important parameters that have been used in estimating the habitat of certain species. Through analyzing these environmental factors, research on the appearance and distribution of whale shark habitats in the Cenderawasih Bay National Park in Papua, Indonesia, utilized field observation data and satellite imagery. This study applied data on the presence of whale sharks and oceanographic parameter data from satellite recordings during 2019 – 2020. Analysis of the relationship and habitat modeling between the monthly presence of whale sharks and environmental parameters was carried out through the Generalized Additive Model (GAM) statistical approach and spatial analysis through the Geographic Information System approach. In the GAM analysis, data on the presence of whale sharks was used as a response variable. In contrast, the predictor variables consisted of SST, SSC, current speed, SSH, and bathymetric data. The results showed that the highest frequency of whale shark presence occurred in the transitional monsoon, with an average presence of 31.77 ± 4.00 %. The study also showed that all predictors showed a highly significant relationship (P < 0.001) to the number of whale sharks present. SST values range from 30.3 – 31.3 °C, SSC of 0.39 – 0.86 mg/L, the current speed of 0.46 – 0.65 m/s, SSH showed 0.63 to 1.00 cm, and bathymetry between 40 – 50 m . In the GAM model, the SST and SSC parameters were the two most important parameters that affect the presence of whale sharks, followed by SSHD, depth (bathymetry), and current parameters.